Thyroid hormone modulation of immunity: Its participation in chronic stress-induced immune alterations - Genaro, Ana Maria (2009)
The interaction between the immune and the neuroendocrine systems involves, in a bidirectional circuit, shared cellular receptors and their coupled signaling pathways. Disruptions of this circuit lead to pathological situations. Between the endocrine factors, thyroid hormones show to play a role in immunomodulation, maintaining immune system homeostasis in response to stress-mediated immunosuppression. Several experimental evidences showed that hypothyroidism leads to a depression of humoral and cell-mediated immune responses, effects that were reversed by restoration of the euthyroid state. By other hand, chronic stressful situations impair T-cell mediated immunity, affecting the intracellular signals involved in lymphocyte activation. Consequently, a reduction in both T-cell dependent antibody production and lymphocyte function were also described. Besides, a decrease in thyroid hormone serum levels was observed in these conditions. These stress-induced endocrine-immune alterations impact in tumor development, as an enhancement of tumor growth was described in animal models of chronic stress. Interestingly, hormone replacement treatment of chronic stressed animals, which restored the euthyroid status, reversed the observed reduction of T-cell responses improving the outcome of tumor bearing animals. These evidences strengthen the important role that thyroid hormones play in immunomodulation, with a special emphasis in their participation as neuroendocrine regulators of stress-mediated immune deficit.